Factors affecting phage D29 infection: a tool to investigate different growth states of mycobacteria - Swift, Benjamin; Gerrard, Zara; Huxley, Jonathan; Rees, Catherine (Public Library of Science, 2014)
Bacteriophages D29 and TM4 are able to infect a wide range of mycobacteria, including pathogenic and non pathogenic species. Successful phage infection of both fast- and slow-growing mycobacteria can be rapidly detected using the phage amplification assay. Using this method, the effect of oxygen limitation during culture of mycobacteria on the success of phage infection was studied. Both D29 and TM4 were able to infect cultures of M. smegmatis and Mycobacterium avium subspecies paratuberculosis (MAP) grown in liquid with aeration. However when cultures were grown under oxygen limiting conditions, only TM4 could productively infect the cells. Cell attachment assays showed that D29 could bind to the cells surface but did not complete the lytic cycle. The ability of D29 to productively infect the cells was rapidly recovered (within 1 day) when the cultures were returned to an aerobic environment and this recovery required de novo RNA synthesis. These results indicated that under oxygen limiting conditions the cells are entering a growth state which inhibits phage D29 replication, and this change in host cell biology which can be detected by using both phage D29 and TM4 in the phage amplification assay.